Pengembangan Buku IPA Berbasis Kearifal Lokal Jambi pada Materi Tekanan serta Getaran dan Gelombang - Jufrida, Jufrida; Basuki, Fibrika Rahmat; Xena, Anta; Hasminingsih, Pretty (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to develop science books based on Jambi local wisdom and improve student learning motivation. This research was a research and development using ADDIE model. The subjects were material experts, media experts and class VIII students of SMPN 1 Muaro Jambi, totaling 30 students. The instruments used in this study were observation sheets, questionnaire needs, material and media validation sheets and student motivation questionnaires. Qualitative data were analyzed descriptively and quantitative data were analyzed using descriptive statistics. This study produced a science book based on Jambi local wisdom about the pressure and vibration and waves. Local wisdom was used as a context to explore scientific concepts. The results of the material expert validation obtained an average score of 4.5 with the category "very good" and the media expert was 4.65 with the category "very good". The results of field trials show that science books based on Jambi local wisdom can increase students' learning motivation with an average score of 4.1 (good category).Abstrak: Penelitian ini bertujuan untuk mengembangkan buku IPA berbasis kearifan lokal Jambi serta meningkatkan motivasi belajar siswa. Penelitian ini merupakan penelitian pengembangan. Subjek penelitian adalah ahli materi, ahli media serta siswa kelas VIII di SMPN 1 Muaro Jambi yang berjumlah 30 siswa. Instrumen yang digunakan dalam penelitian ini lembar observasi, angket kebutuhan  lembar validasi ahli materi dan media serta angket motivasi siswa. Data kualitatif dianalisis secaradeskriptif dan data kuantitatif dianalisis menggunakan statistic deskriptif. Penelitian ini mengahsilkan buku IPA berbasis kearifan lokal Jambi meteri tekanan zat, serta getaran dan gelombang. Kearifan  lokal dijadikan sebagai konteks untuk menggali konsep sains. Hasil validasi ahli materi diperoleh skor rata-rata 4,5 dengan kategori “sangat baik” dan ahli media adalah 4,65 dengan kategori “sangat baik”. Hasil ujicoba lapangan menunjukkan bahwa buku IPA  berbasis kearifan local jambi dapat meningkatkan motivasi belajar siswa dengan skor rata-rata 4,1 (kategori baik).